2016
DOI: 10.1177/1947603516656739
|View full text |Cite
|
Sign up to set email alerts
|

Review of Soluble Biomarkers of Osteoarthritis: Lessons From Animal Models

Abstract: Objective. Osteoarthritis (OA) is one of the leading causes of disability within the adult population. Currently, its diagnosis is mainly based on clinical examination and standard radiography. To date, there is no way to detect the disease at a molecular level, before the appearance of structural changes and symptoms. So an attractive alternative for monitoring OA is the measurement of biochemical markers in blood, urine, or synovial fluid, which could reflect metabolic changes in joint tissue and therefore d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 151 publications
1
19
0
1
Order By: Relevance
“…However, presented results suggest that biomarkers of cartilage metabolism may be more useful for detection of racehorses currently at risk of suffering musculoskeletal injury, which could be of practical importance if regular monitoring of GAG and CPII during racing season was performed. CPII and GAG level changes have been previously demonstrated to correlate with imaging and histopathological outcomes in diagnosis and severity classification of equine osteoarthritis [48, 49], further confirming their relevance as biomarkers of joint injury in that species.…”
Section: Discussionmentioning
confidence: 64%
“…However, presented results suggest that biomarkers of cartilage metabolism may be more useful for detection of racehorses currently at risk of suffering musculoskeletal injury, which could be of practical importance if regular monitoring of GAG and CPII during racing season was performed. CPII and GAG level changes have been previously demonstrated to correlate with imaging and histopathological outcomes in diagnosis and severity classification of equine osteoarthritis [48, 49], further confirming their relevance as biomarkers of joint injury in that species.…”
Section: Discussionmentioning
confidence: 64%
“…Other studies suggested that bone biomarkers like osteopontin and bone sialoprotein are more relevant in the pathogenesis of osteoarthritis [37]. Studies also found that CTX-II correlated better with disease progression of osteoarthritis [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis is a whole joint illness. It is a slow progression long-standing inflammatory disorder that produces gradual articular cartilage destruction, accompanied by alterations of articular soft-tissue and bone and finally leading to pain, joint rigidity, and limb dysfunction (Legrand et al, 2017).…”
Section: Introductionmentioning
confidence: 99%